2022
DOI: 10.21744/ijhms.v5n4.1947
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric aspects and the role of consultation liaison psychiatry (CLP) in traumatic amputation due to electrical burns for adolescents

Abstract: Amputation trauma due to burns is a conflict wound that is very emotionally disturbing, as is often shown on social media and on the small screen to illustrate war, but there are also unintentional events that occur in adolescents that cause burns due to electric shock. The purpose of this paper is to explain the psychiatric aspects and the role of Consultation-Liaison Psychiatry (CLP) in Traumatic Amputation Due to Electrical Burns in Adolescents so that it becomes a consideration in the selection of psychoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…21 Anastomotic leakage, sepsis and anastomotic stenosis dysfunction might develop in the short term after an operation, whereas prematurity and additional anomalies may trigger the problems in the longer term. 7 Laura et al demonstrated that the anastomotic obstruction in 3% of patients, prolonged adynamic ileus in 4% and superficial wound infection in 3%. 8 There is another study which reported that 2.6% of patients had adhesive bowel obstructions and 3.9% had incisional hernias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Anastomotic leakage, sepsis and anastomotic stenosis dysfunction might develop in the short term after an operation, whereas prematurity and additional anomalies may trigger the problems in the longer term. 7 Laura et al demonstrated that the anastomotic obstruction in 3% of patients, prolonged adynamic ileus in 4% and superficial wound infection in 3%. 8 There is another study which reported that 2.6% of patients had adhesive bowel obstructions and 3.9% had incisional hernias.…”
Section: Discussionmentioning
confidence: 98%
“…5 Two decades ago, the CDO survival rate was observed to be 60-70%, but now it exceeds 95%. 6,7 The major objective of the present study was to summarise our clinical experience with 34 infants with duodenal atresia who underwent surgical procedures over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment period by this method is short with low incidence of complications; the occlusal relationship of the posterior teeth was not altered. [2,3] Skeletal and dental bimaxillary protrusion is one of the most factor for which patients seek orthodontic treatment. [4] Posnick et al in their study reported no direct surgical injury the roots in segmental and non-segmental cases.…”
Section: Discussionmentioning
confidence: 99%
“…Orthognathic procedures have been used for correction of skeletal and facial deformities. Anterior Maxillary Osteotomy has been used traditionally for correction of anterior open bite as well as for correction of skeletal discrepancy [1,2]…”
Section: Introductionmentioning
confidence: 99%
“…The Surface Electromyography approach offers many advantages over invasive techniques, including the ease with which the Surface Electromyography signal can be located over the skin and the increased patient comfort. As a result, Surface Electromyography detection of muscle function is more favorable [10].…”
Section: Introductionmentioning
confidence: 99%